A genomic approach to determining the breed composition of pigs kept by smallholders in Uganda - CGIAR Research Program on Livestock (2021)
This is the first report on the breed composition of 'local' pigs in East Africa, determined from a genomic approach. The local Ugandan pig was found to have ancestry contributions from black or belted old British pigs. This information will feed into development of genetic improvement strategies.